2019
DOI: 10.3928/01477447-20190906-06
|View full text |Cite
|
Sign up to set email alerts
|

Negative Pressure Incisional Therapy and Infection After Direct Anterior Approach Primary Total Hip Arthroplasty

Abstract: With the aging of the US population, total hip arthroplasty (THA) is becoming an increasingly common procedure. A major concern after THA is reducing infection rates, as infections can cause devastating complications. Improved sterile technique, standardized infection control protocols, and novel dressings have been used to reduce postoperative surgical site infections (SSIs). The use of either silver-impregnated dry dressings or easily applied incisional negative pressure dressings is aimed at reducing the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Among the 14 studies that evaluated the PREVENA therapy NPWT system, 10 reported decreased rates of SSIs compared with standard dressings. While four studies reported equivalent SSI rates between patients who received NPWT compared with standard dressings, [130][131][132][133] it is important to note that three of these studies were small-scale retrospective analyses. [131][132][133] In contrast, both randomized controlled trials that made this comparison reported decreased SSI rates in patients who received NPWT compared with standard occlusive dressings.…”
Section: Surgical Incise Drapingmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 14 studies that evaluated the PREVENA therapy NPWT system, 10 reported decreased rates of SSIs compared with standard dressings. While four studies reported equivalent SSI rates between patients who received NPWT compared with standard dressings, [130][131][132][133] it is important to note that three of these studies were small-scale retrospective analyses. [131][132][133] In contrast, both randomized controlled trials that made this comparison reported decreased SSI rates in patients who received NPWT compared with standard occlusive dressings.…”
Section: Surgical Incise Drapingmentioning
confidence: 99%
“…While four studies reported equivalent SSI rates between patients who received NPWT compared with standard dressings, [130][131][132][133] it is important to note that three of these studies were small-scale retrospective analyses. [131][132][133] In contrast, both randomized controlled trials that made this comparison reported decreased SSI rates in patients who received NPWT compared with standard occlusive dressings. 46,134 Among the four studies that evaluated the PICO system, [135][136][137][138] three reported decreased SSI rates and one found similar rates between groups (see ►Table 5).…”
Section: Surgical Incise Drapingmentioning
confidence: 99%
“…Experiments and experiences with CINPT have proved useful in the development of a consensus among panels constituted by surgeons [25]. It is estimated that over the past decade, not using ciNPT has increased the cost of treatment for each patient, given the more extended hospitalization stays.…”
Section: Clinical Applications and Analysis Of Cinptmentioning
confidence: 99%
“…Closed incision negative pressure wound therapy (ciNPWT) has been used as a measure to decrease wound drainage, which could potentially help to reduce deep infection [17,18]. These types of dressings have been historically used for complications, non-healing wounds, or as adjuncts between wound debridement and definitive surgical closure [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the use of negative pressure dressings is accepted for the prophylaxis of wound complications in closed surgical wounds in high risk patients. We have previously analyzed the efficacy of negative pressure dressings in primary anterior total hip arthroplasty [18]. There are no specific guidelines that outline indications for the use of incisional negative pressure dressings after primary posterior approach THA.…”
Section: Introductionmentioning
confidence: 99%